Cellular and molecular modifier pathways in tauopathies: the big picture from screening invertebrate models - Hannan, Shabab B.; Dräger, Nina; Rasse, Tobias M.; Voigt, Aaron; Jahn, Thomas R. (Journal of neurochemistry, 2016)
Abnormal tau accumulations were observed and documented in post-mortem brains of patients affected by Alzheimer's disease (AD) long before the identification of mutations in the Microtubule-associated protein tau (MAPT) gene, encoding the tau protein, in a different neurodegenerative disease called Frontotemporal dementia and Parkinsonism linked to chromosome 17 (FTDP-17). The discovery of mutations in the MAPT gene associated with FTDP-17 highlighted that dysfunctions in tau alone are sufficient to cause neurodegeneration. Invertebrate models have been diligently utilized in investigating tauopathies, contributing to the understanding of cellular and molecular pathways involved in disease etiology. An important discovery came with the demonstration that over-expression of human tau in Drosophila leads to premature mortality and neuronal dysfunction including neurodegeneration, recapitulating some key neuropathological features of the human disease. The simplicity of handling invertebrate models combined with the availability of a diverse range of experimental resources make these models, in particular Drosophila a powerful invertebrate screening tool. Consequently, several large-scale screens have been performed using Drosophila, to identify modifiers of tau toxicity. The screens have revealed not only common cellular and molecular pathways, but in some instances the same modifier has been independently identified in two or more screens suggesting a possible role for these modifiers in regulating tau toxicity. The purpose of this review is to discuss the genetic modifier screens on tauopathies performed in Drosophila and C. elegans models, and to highlight the common cellular and molecular pathways that have emerged from these studies. Here, we summarize results of tau toxicity screens providing mechanistic insights into pathological alterations in tauopathies. Key pathways or modifiers that have been identified are associated with a broad range of processes including, but not limited to, phosphorylation, cytoskeleton organization, axonal transport, regulation of cellular proteostasis, transcription, RNA metabolism, cell cycle regulation, and apoptosis. We discuss the utility and application of invertebrate models in elucidating the cellular and molecular functions of novel and uncharacterized disease modifiers identified in large-scale screens as well as for investigating the function of genes identified as risk factors in genome-wide association studies from human patients in the post-genomic era. In this review, we combined and summarized several large-scale modifier screens performed in invertebrate models to identify modifiers of tau toxicity. A summary of the screens show that diverse cellular processes are implicated in the modification of tau toxicity. Kinases and phosphatases are the most predominant class of modifiers followed by components required for cellular proteostasis and axonal transport and cytoskeleton elements.
Gesehen am 30.11.2020